2020
DOI: 10.3766/jaaa.18077
|View full text |Cite
|
Sign up to set email alerts
|

When Can Stable AutoNRT Thresholds be Expected? A Clinical Implication When Fitting Young Children

Abstract: Objective measurements are important for programming cochlear implants in young children and other individuals who cannot participate in behavioral measurements. AutoNRT, the automatic method used to record responses from the auditory nerve in the Cochlear Ltd., implant system, is often used as a basis for estimating the threshold level and comfort level (C-level) for these patients. However, it has not been sufficiently established if AutoNRT measurements remain consistent over time.This study aimed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The procedure was first performed separately for different CI users and for different stimulating electrodes, and then averaged across the individual CI users of the FLEX28 electrode array (i.e., the largest electrode population in this study). The analysis revealed that the 95% confidence intervals of the threshold estimates are maximally ± 1.24 nC wide (mean: 0.59; SD: 0.21), which makes the algorithm suitable also for discovering clinically relevant differences, e.g., in test-retest studies [26][27][28][29][30].…”
Section: Plos Onementioning
confidence: 99%
“…The procedure was first performed separately for different CI users and for different stimulating electrodes, and then averaged across the individual CI users of the FLEX28 electrode array (i.e., the largest electrode population in this study). The analysis revealed that the 95% confidence intervals of the threshold estimates are maximally ± 1.24 nC wide (mean: 0.59; SD: 0.21), which makes the algorithm suitable also for discovering clinically relevant differences, e.g., in test-retest studies [26][27][28][29][30].…”
Section: Plos Onementioning
confidence: 99%